4(2x-1)-6(3-x)=-8

Simple and best practice solution for 4(2x-1)-6(3-x)=-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-1)-6(3-x)=-8 equation:


Simplifying
4(2x + -1) + -6(3 + -1x) = -8

Reorder the terms:
4(-1 + 2x) + -6(3 + -1x) = -8
(-1 * 4 + 2x * 4) + -6(3 + -1x) = -8
(-4 + 8x) + -6(3 + -1x) = -8
-4 + 8x + (3 * -6 + -1x * -6) = -8
-4 + 8x + (-18 + 6x) = -8

Reorder the terms:
-4 + -18 + 8x + 6x = -8

Combine like terms: -4 + -18 = -22
-22 + 8x + 6x = -8

Combine like terms: 8x + 6x = 14x
-22 + 14x = -8

Solving
-22 + 14x = -8

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '22' to each side of the equation.
-22 + 22 + 14x = -8 + 22

Combine like terms: -22 + 22 = 0
0 + 14x = -8 + 22
14x = -8 + 22

Combine like terms: -8 + 22 = 14
14x = 14

Divide each side by '14'.
x = 1

Simplifying
x = 1

See similar equations:

| 17x-34=17 | | 15x+21y=22 | | .5f-2=1.67f | | 2x^2=7x+17 | | 15x-21y=22 | | 3596=58a | | -3b+27=6 | | 67.5=a-24.2 | | 7.8=2m | | 3k=2(k+7) | | 2m^2+5m=2 | | x^2+60=2x+15 | | 17=x | | -5x+7y=10 | | 4(2-3x)+10(x-2)=7 | | -6g+12=12g+12 | | -7(6x+10)=-154 | | 90=2(x^2+60) | | x^6-5x^5-6x^4=0 | | 2x+x=4x | | 3-(12+2x)-6x=15-2x | | (3x+5)-7=0 | | 900000+111111= | | 4y=12-3x | | 2(-9+5x)=52 | | 2(-9+5x)=53 | | 2x-12-2x=4x-12 | | 1/32*12=s | | 3x^4-10x^3-24x^2-6x+5=0 | | 6u^2=-9u | | x-48.12=28.82 | | 6x^2=-9u |

Equations solver categories